Síndrome de apnea hipopnea obstructiva del sueño y excesiva somnolencia diurna en la población de la parroquia Carigán - Castillo Pinta, Cristian Alexander (2019)
Obstructive sleep apnea syndrome (OSAHS) affects the quality and amount of sleep, resulting in excessive daytime sleepiness (SED), recognized as a public health problem because it is an independent risk factor for cardiovascular disease, metabolic syndrome, accidents and poor quality of life. (Guerrero, et al., 2018). In our country there are predisposing factors that make us suspect a high prevalence of OSAHS, so the main objective of this research has the risk of obstructive sleep apnea Excessive Daytime Sleepiness. A study was conducted with a descriptive cross-sectional approach in the Carigan Parish from Loja city, where the STOP-Bang questionnaire and Epworth scale were applied. The results indicated that, of 372 people, 24.70% have an intermediate risk and 9.40% high risk of OSAHS, men are the most affected at 49.69%, with ages 50 to 60 having a higher risk of 66.30%. The most predisposing risk factors in our population were obesity with 92.13%, followed by family history of SAHOS with 42.52% and functional anatomical alterations at 37.80%. In addition, 61.42% of the population with high intermediate-high risk of SAHOS has SED. Concluding that the prototype of a person with SAHOS is an obese 50 to 60 years old man, who has some degree of SED. Keywords: STOP-Bang Questionnaire, Epworth Scale, Daytime Excessive Sleepiness, Sleep Spar, Obesity.